PENGEMBANGAN MEDIA PEMBELAJARAN “SI RAJA” BERBASIS ANDROID PADA PEMBELAJARAN BAHASA JAWA MATERI AKSARA JAWA KELAS V SEKOLAH DASAR - Rizal Efendi; Sukamto; Khusnul Fajriah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background that prompted this research was that in the learning process on Javanese script material it was difficult for teachers to teach Javanese script material and many students had difficulty understanding Javanese script material. In addition, the lack of use of learning media makes students feel bored. Therefore teachers and students need learning media that are interesting, creative, innovative and adapt to changing times. The objectives to be achieved in this study are to explain the characteristics and determine the validity, practicality, and effectiveness of Android-based SI RAJA (Sinau aksara jawa) learning media on Javanese Script Material. The type of research used is research and development (R&D) using the AADIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research was carried out in two elementary schools, namely at Pandean Lamper 05 Elementary School and Barunawati Elementary School which was held on March 15 2023 and March 17 2023. Based on the development that has been carried out, the characteristics of the SI RAJA (Sinau akasara jawa) learning media are that media can be used flexibly, makes it easier for teachers to explain material, makes it easier for students to understand material, is not easily damaged, and is digital-based media to adapt to changing times. The validation results from material experts obtained a percentage of 93% and the validation results from media experts obtained 96.5%. The results of the teacher response questionnaire assessment obtained a percentage of 98.75% and the results of the student response questionnaire assessment obtained a percentage of 100%. The results of the effectiveness test of the two elementary schools show a significance value of less than 0.05. The conclusion is that the Android-based SI RAJA (Sinau aksara jawa) learning media is included in the very good and very feasible category which has fulfilled valid, practical and effective.